Has the Netherlands created a healthy food environment for its citizens? Application of the Food Environment Policy Index (Food-EPI). (30th September 2020) - Djojosoeparto, S K; Kamphuis, C B M; van Lenthe, F; Poelman, M P
Abstract: Background: Healthy food environments have the potential to improve population nutrition and decrease NCDs. The aim of the study was to assess the efforts of the National Government in the Netherlands towards creating healthier food environments using the Healthy Food Environment Policy Index (Food-EPI). Methods: We compiled evidence on national food environment policies in the Netherlands for each of the 47 indicators. This document has been verified for completeness and accuracy by Dutch governmental officials. A panel of independent, nongovernment experts specialized in nutrition, obesity or chronic diseases, was provided with this evidence and rated the extent of implementation of Dutch policies by benchmarking these policies against international best practices during an online survey in May-July 2020. The experts also rated to which extent policies could lead to a decrease or widening of socio-economic inequalities in dietary intake. In addition, experts formulated actions to improve food environment policies in the Netherlands. Results: This is the first interdisciplinary study to assess food environment policies developed and set by the Netherlands. The overview of national level policies resulted in a evidence document, describing policies (or the lack thereof) for each of the 47 indicators. The evidence document shows that the Netherlands has mostly voluntary policies, mainly through the National Prevention Agreement (launched in 2018) and Agreement on Product Improvement (launched in 2014). Results from the online survey and the formulated actions will be presented during the conference. The results will reflect the experts' ratings supported by documented evidence and will provide meaningful guidance to governmental officials and public health advocates in their efforts to improve the food environment policies in the Netherlands.